Strengthening Business Legality through NIB Assistance for Beginner Independent Workers - Setiabudi, Tardi; Rahmawati, Rahmawati; Sampurna, Iman; Assayid, Wandi S. (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2026)
Business legality is a critical prerequisite for micro-enterprises, particularly for Beginner Independent Workers (TKMP) who still face administrative and digital-literacy limitations. This community service program aimed to strengthen the capacity of TKMP-owned micro and small enterprises to obtain a Business Identification Number (NIB) through the Online Single Submission (OSS) system. The program was conducted in Lebak Regency, Banten Province, from 6 to 30 November 2025 and involved 15 participants receiving start-up capital assistance from the Ministry of Manpower of the Republic of Indonesia, none of whom had previously held an NIB. The implementation used a door-to-door approach through planning, implementation, and evaluation stages. Data were collected through direct observation, OSS process checklists, field-constraint notes, and verification of NIB issuance. The results show that all participants successfully obtained NIBs after socialization, technical assistance, and iterative follow-up. The main constraints included limited understanding of OSS, unstable internet signals, difficulties in selecting the appropriate business category or KBLI, and problems in drafting business descriptions. These findings indicate that personalized, adaptive, and contextual mentoring effectively bridges the gap between a digital licensing system and the actual capabilities of novice business actors. The findings highlight that a door-to-door mentoring model is highly relevant for expanding access to business legality in regions with limited digital infrastructure and administrative capacity.